An Assessment of the Effectiveness of Electronic Tax Management Systems in Malawi; Case Study of the Automated System for Customs Data World System (ASYCUDA World) - Nyondo, Wamaka; Arulanandam, Benedict Valentine* (International Journal of Novel Research and Development, 2022)
This study assessed the effectiveness of electronic tax management systems in Malawi taking a case study of AYSYCUDA World system inspired by the fact that there was a little local research in this area hence the remained unknown of the effectiveness of these introduced systems. The study looked at the user satisfaction of the electronic tax management systems, the cost effectiveness of electronic tax management systems and the time effectiveness of the electronic tax management systems. Problems affecting the performance of these systems were also analyzed and possible solutions provided. The study adopted a case study and cross-sectional survey design to obtain information on electronic tax management system effectiveness taking into account of ASYCUDA World users. A sample of 79 respondents were selected using a simple random selection. Data was collected by using questionnaires (with a 96% response rate) and documentary review. Quantitative data were analyzed by using Statistical Package for Social Science (SPSS) and Microsoft Excel while qualitative required the use of Microsoft Word. Findings revealed that the users are satisfied with the systems although there are some structures that are hindering the user satisfaction hence affecting the effectiveness of the electronic tax management systems. It also revealed that the ASYCUDA World is not cost effective although the cost benefit analysis indicated that the benefits that are being realized by the user are outweighing the costs. The ASYCUDA World has also led to the reduction in the time taken to clear goods due to easiness of payments. However, the study revealed some of the challenges affecting the effectiveness of electronic tax management systems including the ASYCUDA World. These problems were: lack of user awareness campaigns, power outages, poor ICT infrastructures and poor network connectivity. The study recommended that the user awareness campaigns be provided, MRA should improve on solving the system query once received from the users, and MRA improve on the accessibility and availability of electronic tax management systems that is through different electronic gadgets like phones and tablets.